2020
DOI: 10.31235/osf.io/kwf98
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sweet Spots of Residual Deterrence: A Randomized Crossover Experiment in Minimalist Police Patrol

Abstract: In this article, we examine how communities can maximize deterrence of crime while minimizing cost and police intrusion on public life. Using 3,720 hot spot-days, we show that the “sweet spot” duration of police absence, to maximize the residual deterrence of crime, was a full four days after the last day of targeting police patrol at each hot spot. Over a 248-day period, we randomly reshuffled 15 separate hot spots daily into either treatment (targeted police patrols) or control (no targeted patrols) for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 41 publications
1
46
1
Order By: Relevance
“…All eligible studies implemented quantitative research designs. About three quarters of the selected studies implemented experimental research designs (n = 36), of which 13 conducted randomized controlled trials (e.g., Sherman et al 1995b, Sherman et al 1995a, Ratcliffe et al 2011, Taylor et al 2011 2014, Barnes et al 2020). On average police presence was monitored for approximately 350 days (SD ~ 483 days).…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…All eligible studies implemented quantitative research designs. About three quarters of the selected studies implemented experimental research designs (n = 36), of which 13 conducted randomized controlled trials (e.g., Sherman et al 1995b, Sherman et al 1995a, Ratcliffe et al 2011, Taylor et al 2011 2014, Barnes et al 2020). On average police presence was monitored for approximately 350 days (SD ~ 483 days).…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
“…This can be well linked to the extension of the Koper curve (Koper 1995) and residual deterrence. Residual deterrence describes the effects of police presence, e.g., reduction in crime, persist for a certain amount of time even after officers left the place (Stephensen 2017, Williams and Coupe 2017, Barnes et al 2020. Initial deterrence decay deals with the duration of reduction effects and is interested in how fast deterrent effects decay (Sisiopiku and Patel 1999, Sorg et al 2013, Novak et al 2016.…”
Section: Length Vs Frequency Of Police Presencementioning
confidence: 99%
See 2 more Smart Citations
“…Ariel et al (2020) reported that in a randomized trial in the London Underground, 15-min patrols on over 50 randomly selected hot spot platforms 4 days a week reduced crime across 7 days per week, compared with having no regular patrols on some 50 other equally "hot" high-crime frequency platforms. Most recently, Barnes et al (2020) have reported that the effects of one randomly assigned 15-min visit produced residual deterrent effects lasting for up to 4 days of no further patrols.…”
Section: Research Questionmentioning
confidence: 99%